Real Food Education as a Strategy For Preventing Non-Communicable Diseases in Elementary School Students - Riska Epina Hayu; Eva Mayasari; Rika Mianna; Shinta Wulansari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Excessive and continuous consumption of junk food will impact children's health, especially it can cause nutritional disorders at an early age which leads to an increased risk of non-communicable diseases. Cases of Non-Communicable Diseases (NCDs) or chronic diseases such as obesity, diabetes and kidney failure in children are caused by consumption patterns with unbalanced nutrition from an early age experiencing an increasing trend. Community service with the theme of Real Food Consumption Education as an Effort to Prevent Non-Communicable Diseases in Elementary School Children was carried out on Monday, June 23, 2025 for fifth grade students at 008 Public Elementary School, Lubuk Siam Village. This educational implementation was carried out by explaining the material and also followed by games using pictures of various types of real food and fast food. After the presentation of the material, students participated in games using cards containing pictures of various examples of real food and fast food. This community service aims to educate school-age children to be able to choose good and healthy foods to prevent non-communicable diseases in children. In addition to children, parents and teachers also have a role to understand the importance of providing healthy nutrition, especially in consuming sugar, salt and fat. Providing good nutrition to children is one way to fulfill their right to health, a shared endeavor. This community service project utilized PowerPoint presentations and handouts. Based on the results of the community service activities, it was discovered that students did not yet fully understand the difference between real food and fast food. Therefore, ongoing education on the importance of consuming natural foods is essential to prevent the occurrence of non-communicable diseases in the future.